Digital Marketing Curriculum Transformation: Increasing Students' E-Commerce Creativity and Digital Ethical Awareness at Distance College - Kadarisman Kadarisman; Romi Siswanto; Yati Yati; Fitra Jaya; Sucipto Sucipto (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the impact of the transformation of the Digital Marketing curriculum on students' creativity in e-commerce and their awareness of digital security and ethics at distance learning universities. Involving 89 respondents across Indonesia, this research employed a quantitative approach and linear regression analysis to examine the relationship between variables. The results indicate a significant positive influence between the transformation of the Digital Marketing curriculum and students' creativity, with a correlation coefficient (r) of 0.78 and p-value < 0.05. This suggests that improving the quality of the curriculum can stimulate students' creativity in developing innovative marketing strategies. The study also reveals that curriculum transformation incorporating interactive modules and project-based simulations enhances students' awareness of digital security practices and ethics, aligning with previous research by Jones and Jones (2022) and Nwankwo and Ayoade (2022). Integrating ethical and security aspects into course materials helps students understand the importance of data privacy and responsible behavior in digital environments. These findings emphasize the need for the continuous development of a comprehensive Digital Marketing curriculum that includes practical, ethical, and creative approaches. The practical implications of this research direct universities to enrich their course content with real-world case projects, cybersecurity training, and collaboration with industry professionals to provide deeper insights. The results of this study are expected to serve as a foundation for developing curricula that equip students not only with technical skills but also prepare them to become creative and responsible professionals in the digital era.